Economic Coverage of the Fair Labor Standards Act - Weiss, Harry (Quarterly Journal of Economics, 1944)
Introduction: general defects, 460. — Basic principles of coverage, 461. — Extent of coverage in relation to total employment, 462. — Groups completely exempt from the Act, 468. — Major problems involved in present coverage: competing industries in different positions, 472; gold mining, 473; wholesaling, 474; retailing, 474; exemptions, 476; construction, 476; maintenance, 477. — Suggested revisions of the Act, 477.